A study on impacts of parental divorce towards students at UiTM Malacca City Campus / Nor Fiqa Aida Sabri and Nurul Izati Zakaria - Sabri, Nor Fiqa Aida; Zakaria, Nurul Izati (Faculty of Administrative Science and Policy Studies, 2012)
This study examined the impact of parental divorce on the affective development of students, in order to assess the needs of this group for guidance, support, services, policies, and legislation. The purpose of this study was to determine the impact of parental divorce on the development of students (young adults). It was hoped that results from this study at the micro level might help professionals such as psychologists, counsellor, therapists, university professors, health care providers, family law attorneys, and legislators who deal with this population directly or indirectly, to be more sensitive to the needs of this group and to provide the needed guidance, support, services, policies, and legislation. At the macro level, it was hoped that results would add to the body of knowledge on divorcing families. In this research, the study has been conducted in UiTM Malacca city campus at Jalan Hang Tuah, Melaka. The students are selected by using the Simple Random Sampling Method in which every student from the population of 130 has an equal chance of being selected. We need to have a numbered list of the students of the parental divorce. Sample students are then chosen based on Morgan table. Researcher conducted questionnaires survey instrument in gaining the data for research. Respondents were asked to answer the questionnaires but only 97 respondents were obtained and analyzed. Data are analyzed using Reliability test, Correlations analysis and Descriptive analysis through Statistical Package for Social Science (SPSS) computerized programs. The result of the findings shows that social life is the most influential impacts to the students of parental divorce in UiTM Malacca City Campus.